Evaluation and Development Strategy of The Minapolitan Area in Pasir Sakti Sub-District, Lampung Timur Regency - Puspita, Ni Putu Rekha; Rustiadi, Ernan; Kolopaking, Lala M. (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2025)
The minapolitan concept aimed to accelerate Indonesian rural development and reduce the inequality of development between urban-rural and urban disparity. One of the cultivation-based minapolitan areas in Indonesia is in Pasir Sakti Sub-District, East Lampung Regency with the Vaname shrimp commodity. The problems in this minapolitan area are including the inefficiency of pond farming management, restrained land for pond farmers so it difficult to obtain labor for the community, limited market information, unstable production quantities sometimes fail to fulfill market demand, and microfinancing institutions aren't working properly. This research aims to evaluate the program and set the next development strategy in the Pasir Sakti Minapolitan Area. The research was undertaken through several questionnaire surveys of pond farmers and the experts, followed by discussions with some experts to analyze the factors that affect the development of this minapolitan area with Internal Factors Evaluation (IFE) and External Factors Evaluation (EFE) Analysis, and set development strategies using The Quantitative Strategic Planning Matrix (QSPM) analysis. This research results indicate that the minapolitan area program is 84.848% in synergy with existing regional policies, the environment evaluation of the minapolitan area is 85.82% feasible, the institutional support evaluation for minapolitan area is 75.42% feasible, and the IFE analysis results in a score of 2.63 and EFE results with a score of 3.03. These values exceed the average score of 2.5, which indicates that the internal condition of the region is not deteriorating and is ready to take advantage of opportunities and overcome threats. The strategic objectives for the development of the minapolitan area are to improve the quality and participation of stakeholders, increase supporting facilities, anticipate environmental damage planning and law enforcement, and improve cultivation systems.